Employee Turnover and Education Sector Service Delivery in Local Governments in Uganda: A Case Study of Rubanda District Local Government. - Mucunguzi, Elly (Kabale University, 2024)
The purpose of this study was to investigate how employee turnover affects education service delivery in Rubanda District Local Government. The objectives that guided the study were: to examine the extent of the problem of labour turn over and its causes in Rubanda district; to establish the effect of employee turnover in the education sector service delivery in Rubanda district, to identify the strategies to reduce on employee turnover in the education sector in Rubanda district, while the outcome variable was the provision of services in the education sector. The cross-sectional survey was followed in the study. Data from 165 respondents was gathered; quantitative and qualitative analysis was also performed. Frequency tables were employed to describe the data since descriptive analysis required presentation of a single variable and its characteristics. A Pearson correlation matrix was used to determine the correlations between the predictor factors and the dependent variable at the bivariate level. To fit the data, linear regression models were employed. According to research results from the regression models, the provision of services in the education sector in Rubanda District local government is positively impacted by the extent of the problem of labour turnover and its causes (R=7612); the effects of employee turnover on the education sector in Rubanda district local government (R=654); and strategies to reduce employee turnover on education in Rubanda district local government(R=866). The fundamental finding of this study was that, to the bigger extent, labour turnover and its causes affect education sector service delivery in Rubanda district local government and there are strategies that could be employed to reduce employee turnover in the education sector in Rubanda district local government. Therefore, this study recommends that Rubanda district local government should concentrate on implementing the identified strategies to reduce employee turnover, thereby enhancing the provision of education services.